1991
DOI: 10.1139/z91-072
|View full text |Cite
|
Sign up to set email alerts
|

On sex-specific foraging behaviour in the Willow Warbler, Phylloscopus trochilus

Abstract: 1 . On sex-specific foraging behaviour in the Willow Warbler, Phylloscopus trochilus. Can. J. Zool. 69: 462-470. The foraging behaviour of Willow Warblers (Phylloscopus trochilus) in relation to the availability of their insect prey was studied at the Tovetorp Field Station and at the Royal Park of Djurgirden, Stockholm, Sweden, from 1985 through 1989. The numbers and types of arthropods available to Willow Warblers fluctuated throughout the breeding season. In general, most arthropods were found on the unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Larger species may prefer more productive habitats, if the insects occupying these habitats are larger than average, as Shvarts and Demin (1994) found for ground-dwelling insects. This idea is supported by the finding of Nyström (1990) that deciduous trees hold a higher proportion of large arthropods than coniferous trees. Also, Price (1991) found that larger Phylloscopus species prefer larger prey items.…”
Section: Discussionmentioning
confidence: 75%
“…Larger species may prefer more productive habitats, if the insects occupying these habitats are larger than average, as Shvarts and Demin (1994) found for ground-dwelling insects. This idea is supported by the finding of Nyström (1990) that deciduous trees hold a higher proportion of large arthropods than coniferous trees. Also, Price (1991) found that larger Phylloscopus species prefer larger prey items.…”
Section: Discussionmentioning
confidence: 75%
“…Unassisted females need to catch prey at a higher rate than assisted females (Sasva¨ri 1986;Pinxten & Eens 1994;Aho et al 1997) and they may achieve this by increasing search speed (Sasva¨ri 1986;Aho et al 1997;W. Forstmeier, unpublished data) and by using more energy-consuming foraging manoeuvres (NystrÎm 1990;W. Forstmeier, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…when they arrive on breeding territories about 11 days before females. The arrival of females is correlated with the female mating order (Nystrom 1987(Nystrom , 1991Radesater et al 1987). The male provides a territory as a resource necessary for successful breeding, which is defended throughout the breeding season.…”
Section: Introductionmentioning
confidence: 99%
“…They did not measure food abundance or consider the influence of male body condition on song rate, and they found no correlation between male mass or wing length and arrival date. Nystrom (1991) also reported that during the first week at a territory, males, except when they were gleaning, used more energy-demanding foraging methods, such as hovering and fly catching, when foraging on the sparse food resources that were available. Small males, then, should be favoured and gain a high body condition and fighting capability, since they can acquire the energy required for body maintenance with less effort (Gustafsson 1988).…”
Section: Introductionmentioning
confidence: 99%